Recent advances in dermal fibroblast senescence and skin aging: unraveling mechanisms and pioneering therapeutic strategies - Nan, Li; Guo, Pengchao; Hui, Wang; Xia, Fang; Yi, Chenggang (Frontiers in Pharmacology, 2025)
Aging is a multifactorial process that affects skin integrity through the progressive decline of dermal fibroblast function. Dermal fibroblasts are key regulators of extracellular matrix (ECM) composition, wound healing, and tissue homeostasis. However, their dysfunction contributes to structural deterioration, chronic inflammation, and impaired regenerative capacity. Cellular senescence, a fundamental characteristic of aging, results in the buildup of senescent fibroblasts that release growth factors, matrix-degrading enzymes, and pro-inflammatory cytokines, known as the senescence-associated secretory phenotype (SASP). This study examines the impact of fibroblast senescence on dermal aging, highlighting mechanisms such as DNA damage, mitochondrial dysfunction, oxidative stress, and telomere attrition. The role of SASP-driven ECM degradation, matrix metalloproteinases (MMPs) activation, and fibroblast-keratinocyte communication breakdown are explored, demonstrating their collective contribution to skin aging. Additionally, key signaling pathways, including p16INK4a/RB, p53, NF-κB, mTOR, and TGF-β, are implicated in fibroblast senescence and chronic inflammation. Recent advancements in therapeutic strategies targeting fibroblast aging, such as senolytics, extracellular vesicle-based interventions, and metabolic reprogramming, offer promising avenues for skin rejuvenation. This review delves into the molecular and cellular dynamics of dermal fibroblast aging, emphasizing their relevance for developing novel anti-aging interventions.